Konsep Pisah Ranjang dalam Sifat tak-terputuskan Perkawinan Katolik: Analisis Kanon 1151-1155 - Adon, Mathias; Dominggus, Hyronimus (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Abstract: The purpose of this study is to examine the meaning of "separate bed" in the concept of the unbreakable nature of a Catholic marriage. The Catholic Church in essence highly values ​​the essential nature of marriage, which is one and indivisible. This also emphasizes that the Catholic Church does not want a divorce. The church only recognizes "bed separation" in the context of husband and wife who want to separate. The Code of Canon Law (Can. 1151-1155) is very clear and detailed what this “bed separation” means. In addition, "separate bed" is an opportunity for husband and wife who are separated to introspect each other. This research was conducted using a library research method which is descriptive in a Catholic Church Law perspective. From this research, We found the basic point of what the meaning of “separation of bed” in the Catholic Church is that distinguishes it from the road to divorce. In other words, separation in the Catholic Church will not eliminate the unbreakable nature of marriage, unless death separates it.Abstrak: Penelitian studi ini memiliki tujuan menelaah makna “pisah ranjang” dalam konsep sifat tak-terputuskannya Perkawinan Katolik. Gereja Katolik pada intinya sangat menghargai sifat hakiki dalam perkawinan yakni satu dan tak-terputuskan. Hal ini pun mau menegaskan bahwa Gereja Katolik tidak menginginkan adanya perceraian. Gereja hanya mengenal “pisah ranjang” untuk konteks suami-istri yang memang ingin berpisah. Kitab Hukum Kanonik (Kan. 1151-1155) dengan sangat jelas dan terperinci bagaimana arti dari “pisah ranjang” ini. Selain itu, “pisah ranjang” sejatinya menjadi kesempatan untuk suami-istri yang berpisah untuk saling menginstropeksi diri. Penelitian ini dilakukan dengan menggunakan metode penelitian studi pustaka yang bersifat deskriptif dalam perspektif Hukum Gereja Katolik. Dari penelitian ini, kami menemukan titik dasar apa makna “pisah ranjang” dalam Gereja Katolik yang membedakannya dengan jalan menuju perceraian. Dengan kata lain, berpisah dalam Gereja Katolik tidak akan menghilangkan sifat tak-terputuskan Perkawinan, kecuali maut memisahkannya.